Essential Roles of Toll-Like Receptors in Atherosclerosis - Lin, Juntang; Kakkar, Vijay; Lu, Xinjie (Current Medicinal Chemistry, 2016)
Atherosclerosis is driven by inflammation with an involvement of innate and adaptive immune responses. Toll-like receptors, the well-defined pattern recognition receptors of the immune system, play a central role in macrophage activation. Toll-like receptors recognize pathogen-associated molecular patterns expressed by a wide range of infectious agents and provide a strong link between local innate and adaptive immunity. Activation of these receptors triggers an intracellular signaling cascade mediated through myeloid differentiation factor 88 or toll/interleukin-1 receptor-domain-containing adapter-inducing interferon-β, leading to the secretion of proand anti-inflammatory cytokines. Engagement of Toll-like receptors with their ligands induces leukocyte recruitment and enhances matrix metalloproteinase expression within atherosclerotic lesions. Recently certain Toll-like receptors have shown a protective role in atherosclerosis. TLRs, therefore, represent an important link between inflammation and atheroma, making them attractive targets for the treatment of atherosclerosis. This review will briefly describe the general biological structure and potential roles of Toll-like receptors as therapeutic targets for the treatment of atherosclerosis and highlight the potential challenges on Toll-like receptor- based therapy in cardiovascular disease.
Keywords: cardiovascular disease